The Effect of Company Size, Profitability, Leverage and Audit Quality on Tax Avoidance Of Manufacturing Companies Listed on The Indonesia Stock Exchange in 2019-2023 - Rani Putri Nan JUWITA; Tri Darma Rosmala SARI (International Journal of Environmental, Sustainability, and Social Science, 2025)
This study aims to empirically test the effect of Company Size, Profitability, Leverage and Audit Quality on Tax Avoidance in Manufacturing companies listed on the Indonesia Stock Exchange for the period 2019-2023. The research method uses a quantitative analysis approach. The sampling technique employed in this study utilizes a purposive sampling method involving a sample of 54 companies. This research was conducted on manufacturing companies listed on the Indonesia Stock Exchange for the period 2019-2023. The data used in this study are secondary data obtained from the published financial statements of manufacturing companies. The data analysis methods used include descriptive statistics, classical assumption tests, t-tests, and coefficient of determination tests. The results of this study state that Company Size has no effect on Tax Avoidance listed on the Indonesia Stock Exchange for the period 2019-2023; Profitability hurts Tax Avoidance listed on the Indonesia Stock Exchange for the period 2019-2023; Leverage has no effect on Tax Avoidance listed on the Indonesia Stock Exchange for the period 2019-2023; Audit quality has a positive effect on Tax Avoidance listed on the Indonesia Stock Exchange for the 2019-2023 period.